2022
DOI: 10.1371/journal.pgen.1010076
|View full text |Cite
|
Sign up to set email alerts
|

eQTL mapping using allele-specific count data is computationally feasible, powerful, and provides individual-specific estimates of genetic effects

Abstract: Using information from allele-specific gene expression (ASE) can improve the power to map gene expression quantitative trait loci (eQTLs). However, such practice has been limited, partly due to computational challenges and lack of clarification on the size of power gain or new findings besides improved power. We have developed geoP, a computationally efficient method to estimate permutation p-values, which makes it computationally feasible to perform eQTL mapping with ASE counts for large cohorts. We have appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…When performing bulk eQTL, CSeQTL is equivalent to the TReCASE method [28] that combines total expression and allele-specific expression to improve the power of eQTL mapping. Consistent with our previous results [11, 28], CSeQTL has much higher power than OLS for bulk eQTL mapping. For example, considering the results for CMC schizophrenia samples (n=250), for bulk eQTL mapping, CSeQTL and OLS identified around 10,000 and 3,000 eGenes (genes with at least one significant eQTL) respectively.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…When performing bulk eQTL, CSeQTL is equivalent to the TReCASE method [28] that combines total expression and allele-specific expression to improve the power of eQTL mapping. Consistent with our previous results [11, 28], CSeQTL has much higher power than OLS for bulk eQTL mapping. For example, considering the results for CMC schizophrenia samples (n=250), for bulk eQTL mapping, CSeQTL and OLS identified around 10,000 and 3,000 eGenes (genes with at least one significant eQTL) respectively.…”
Section: Resultssupporting
confidence: 92%
“…A brute-force implementation, which requires permuting the data many times and running CSeQTL on each permuted dataset, is computationally prohibitive. Instead, we employed a computationally efficient method named geoP [11, 27] that calculates the permutation p-value by estimating the effect number of independent tests. To account for multiple testing across genes, we selected a permutation p-value cutoff to control the false discovery rate (FDR).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also be of interest to detect in which cell types the allelic signal may be strongest or exclusively present, as has been investigated in recent methods for single cell allelic expression or accessibility datasets [7880]. Finally, we note that a number of methods have shown that AI can be effectively integrated with total expression across individuals of all three genotypes [5, 8184, 13]. This approach uses more information, and so should produce a gain in sensitivity, as well as extending beyond genes harboring exonic variants, which is a limitation for AI-based methods.…”
Section: Discussionmentioning
confidence: 99%